Using video to support in-service teacher professional development: the state of the field, limitations and possibilities. Issue 1 (1st January 2018) - Major, Louis; Watson, Steven
Abstract: Video is increasingly used to support in-service teacher professional development (TPD). Advances in affordability and usability of technology mean that interest is set to develop further. Studies in this area are diverse in terms of scale, methodology and context. This places limitations on undertaking a systematic review; therefore the authors use a scoping review approach. Their analysis involves 82 studies from which they thematise subtopics and assess research characteristics. This provides a much-needed analysis to inform researchers and practitioners. Additionally, the authors identify robust studies that consider the effect of video on teacher cognition and classroom practice. A consistent finding is that video is effective when used as part of TPD. Since studies largely use thematic qualitative analysis, however, this consensus needs further examination. Further qualitative and quantitative research is needed to identify how the use of video impacts on classroom practices.